Respuestas
Respuesta dada por:
2
Tenemos:
![y = {x}^{2} - 2 \\ y = 2x y = {x}^{2} - 2 \\ y = 2x](https://tex.z-dn.net/?f=y+%3D++%7Bx%7D%5E%7B2%7D+-+2++%5C%5C++y+%3D+2x)
Si X vale -1:
![y( - 1) = 2( - 1) = - 2 y( - 1) = 2( - 1) = - 2](https://tex.z-dn.net/?f=y%28+-+1%29+%3D+2%28+-+1%29+%3D++-+2)
La pendiente en ese punto vale -2.
La ecuación de la recta será:
![- 1 = - 2( - 1) + n \\ n = - 3 \\ y = - 2x - 3 - 1 = - 2( - 1) + n \\ n = - 3 \\ y = - 2x - 3](https://tex.z-dn.net/?f=+-+1+%3D++-+2%28+-+1%29+%2B+n+%5C%5C+n+%3D++-+3+%5C%5C+y+%3D++-+2x+-+3)
Si X vale -1:
La pendiente en ese punto vale -2.
La ecuación de la recta será:
pvatxyx:
MUCHAS GRACIASSS♡♡
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años